3D QSAR Pharmacophore Based Virtual Screening for Identification of Potential Inhibitors for CDC25B. (April 2018) - Ma, Ying; Li, Hong-Lian; Chen, Xiu-Bo; Jin, Wen-Yan; Zhou, Hui; Ma, Ying; Wang, Run-Ling
Graphical abstract: Highlights: The technique of "Hypogen" was used to build the pharmacophore model Hypo-1-CDC25B. 9 potential CDC25B inhibitors were discovered by pharmcophore-based virtual screening and docking analysis. Compared with the existing inhibitor-compound 1, ZINC7959507 had better conformation in binding to CDC25B in both Docking and Molecular Dynamics simulations. Abstract: Owing to its fundamental roles in cell cycle phases, the cell division cycle 25B (CDC25B) was broadly considered as potent clinical drug target for cancers. In this study, 3D QSAR pharmacophore models for CDC25B inhibitors were developed by the module of Hypogen. Three methods (cost analysis, test set prediction, and Fisher's test) were applied to validate that the models could be used to predict the biological activities of compounds. Subsequently, 26 compounds satisfied Lipinski's rule of five were obtained by the virtual screening of the Hypo-1-CDC25B against ZINC databases. It was then discovered that 9 identified molecules had better binding affinity than a known CDC25B inhibitors-compound 1 using docking studies. The molecular dynamics simulations showed that the compound had favorable conformations for binding to the CDC25B. Thus, our findings here would be helpful to discover potent lead compounds for the treatment of cancers.